EVALUASI KERUSAKAN DAN OVERLAY RUAS JALAN UPUA BAGUALA KOTA AMBON - Mochsin, Fakri Hidayat; Johny, Soumokil Hengki; Lattar, Sjafrudin (Menara: Jurnal Teknik Sipil, 2024)
ABSTRACT The method used is the method of BINA MARGA (2005), namely by conducting a survey in the field and the results of the survey are divided into several segments. The damage seen includes cracking , rutting , potholes or patches , and depression . Based on the results of the analysis using the BINA MARGA Method, it is necessary to use a 10 cm thick Laston pavement , 20 cm thick foundation layer ( class A aggregate ), and 20 cm thick carry-on foundation layer ( class B aggregate) so that the road becomes more suitable for driving. through all of society.